Martin's dream day - Kelley, Kitty (Atheneum Books for Young Readers, 2017)
Recounts Martin Luther King Jr.'s iconic "I Have a Dream" speech during the March on Washington for Jobs and Freedom, describing the hardships and triumphs King encountered along his journey.